Characterization and valorization of biomass ashes - Trivedi, Nikhilesh S.; Mandavgane, Sachin A.; Mehetre, Sayaji; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2016)
In India, farming is the primary source of income for many families. Following each harvest, a huge amount of biomass is generated. These are generally discarded as "agrowaste," but recent reports have indicated several beneficial uses for these biomasses and their ashes. However, before the utilization of biomass ashes (BMAs), their chemical and physical properties need to be investigated (characterized) so as to utilize their potential benefit to the fullest. In this paper, eight different biomass ashes (soybean plant ash, mustard plant ash, maize ash, groundnut plant ash, cotton plant ash, wheat plant ash, pigeon peas ash, and groundnut shell ash) were characterized, and their chemical properties are discussed. Surface chemical composition analysis, proximate analysis, and ultimate analysis were performed on all BMA samples, and properties such as porosity, particle density, bulk density, point of zero charge, BET surface area, water-absorption capacity, and bulk parameters such as surface pH and surface charges were determined. BMAs were characterized by SEM and FTIR. The surface areas of biomass ashes vary from 1.9 to 46 m(2)/g, and point of zero charge for all BMAs exceed 9.8, which confirmed the alkaline nature of these samples. Based on the chemical composition, BMAs are categorized into four types (S, C, K, and CK), and their utilization is proposed based on the type. BMAs find applications in agriculture and construction industries; glass, rubber, and zeolite manufacturing; and in adsorption (as a source of silica/zeolites). The paper also discusses the research challenges and opportunities in utilization of BMAs.

Mustard plant ash: a source of micronutrient and an adsorbent for removal of 2,4-dichlorophenoxyacetic acid - Trivedi, Nikhilesh S.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2016)
The work highlights the utilization of an agricultural waste mustard plant ash (MPA) as a soil additive and an adsorbent. MPA was characterized by X-ray fluorescence (XRF), energy-dispersive X-ray spectroscopy (EDX), proximate analysis, CHNS analysis, Brunauer-Emmett-Teller (BET) surface area analysis, zeta potential measurements, Fourier transform infrared (FTIR), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). XRF analysis confirmed the presence of CaO (31.35 %), K2O (18.55 %), and P2O5 (6.99 %), all of which act as micronutrients to plants. EDX also confirms high amount of elemental O, Ca, K, and P. The adsorptive ability of MPA was investigated using a commonly used herbicide, 2,4-dichlorophenoxyacetic acid (2,4-D), as a representative chemical. Batch adsorption experiments were conducted to study the effect of different operational parameters such as adsorbent dose, initial 2,4-D concentration, contact time, and temperature on the adsorption process. Data from experiments were fitted to various kinetic and isothermal models. The pseudo-second-order kinetic model was found to show the best fit (R (2) > 0.99), with the highest k (2) value of the order 10(5). Based on the study results, dosage of MPA/hectare for different crops has been recommended for effective removal of 2,4-D. To our knowledge, this is the first study in which MPA has been characterized in detail and investigated for dual applications (as an adsorbent and as a soil additive).